Zinc Supplementation as an Adjunctive Therapy in Children with Acute Respiratory Tract Infections: A Literature Review - Dewanti, Nia Pradnya; Yuktasya, Putu Bagus Ananta; Faradina, M Arasy (Jurnal Indonesia Sosial Sains, 2026)
Acute respiratory infection (ARI) is one of the leading causes of morbidity and mortality among children worldwide, particularly in low- and middle-income countries. Children are more vulnerable to ARI because their respiratory defense mechanisms, including mucociliary clearance and immune responses, are not yet fully developed. This condition increases the risk of infection and the severity of respiratory illnesses. Zinc is an essential micronutrient that plays a crucial role in various enzymatic processes, cellular metabolism, and the regulation of the immune system. Zinc deficiency has been associated with impaired immune function, making children more susceptible to infectious diseases, including ARI. Therefore, zinc supplementation has been proposed as a potential adjunct therapy to improve clinical outcomes in children with ARI. This literature review aimed to evaluate evidence from clinical trials regarding the effectiveness of zinc supplementation as an adjunct therapy in pediatric ARI. A systematic search was conducted using the PubMed, Cochrane Library, and ScienceDirect databases, and study selection and synthesis followed the PRISMA approach. A total of 11 clinical trials were included in this review. The findings demonstrated inconsistent results in terms of symptom duration, severity reduction, and recovery time among children receiving zinc supplementation. Based on the current evidence, zinc supplementation cannot yet be recommended as a routine adjunct therapy for the management of ARI in children, and further high-quality, well-designed clinical trials are needed to clarify its potential benefits.